The Students’ Perception on Blended Learning Used by the English Teachers at SMAN 3 Maros - Muhammad Fadli; Andi Tenri Ampa; Nur Qalbi (ELT Worldwide: Journal of English Language Teaching, 2022)
A person's habit of putting what they have learned into practice is a metric that can be used to measure perception, regardless of whether the person agrees with, disagrees with, or justifies what they have learned. In this study, 35 students from class XII MIPA 4 SMAN 3 Maros participated, and descriptive qualitative research methods were employed to conduct the study. The purpose of the research was to investigate the perspectives of students towards blended learning in English. In particular during the COVID-19 pandemic, where there were no dominants in blended learning, students felt that offline learning was still the most important thing major compared to online learning. The conclusion of the students' perceptions on blended learning assists students in accepting their right consciousness to learn English. The study implies a pedagogical perspective into EFL senior high school students’ view towards blended learning post-pandemic time where offline and online classes have only recently begun in Indonesia.